Optimising laboratory-rearing parameters for anopheles funestus to enhance scalability toward the sterile insect technique - Niain’ny Felamboahangy, Lalasoa (University of the Witwatersrand, Johannesburg, 2023)
The plateauing of gains in the fight against malaria, partly due to insecticide resistance in malaria vector mosquitoes, is a threat to malaria control. Additional vector control tools like the sterile insect technique (SIT) are being evaluated. Anopheles funestus, a main malaria vector in Africa, has not yet been evaluated for control using SIT partly due to difficulties in its colonisation. To proceed with SIT for this species, knowledge of their optimal laboratory-rearing conditions is critical. To optimise An. funestus laboratory-rearing conditions, this study investigated the effect of using an artificial blood-feeding system or anaesthetised guinea pig on fecundity and fertility. Different larval diet doses and larval rearing densities were determined using a life-table approach. Finally, a range of irradiation doses were used to determine the optimal dose which induces sterility in An. funestus males without impacting the ability of the sterile males’ to compete with fertile males to mate with fertile females. Subsequently, mating competitiveness under laboratory conditions of An. funestus males irradiated at 120 Gy across three different ratios of fertile: irradiated males were performed. Results showed that fecundity was three times higher in females blood-fed on anaesthetised guinea pig compared to those blood-fed on the artificial blood-feeding system using bovine blood. Increasing the blood-meal frequency using the artificial blood-feeding system increased egg production, although it was not statistically significant. There were no significant differences between the egg fertility from females that fed on guinea pig or those fed on the artificial blood-feeding system using bovine blood. Anopheles funestus larvae fed with a food dose of 0.04 mg/larva and reared at a density of 0.48 larvae/cm2 resulted in optimal developmental time and pupal production. Furthermore, irradiation of male pupae at different doses did not affect adult emergence regardless of the dose used, however, it correlated negatively with longevity and fertility. Irradiation at doses greater than 100 Gy resulted in a significant difference in both fecundity and fertility. The average mating competitiveness value of An. funestus males irradiated at 120 Gy was 1.24, decreased from 2.63 to 0.27 for different ratios of sterile male: fertile male: fertile female 1:1:1 to 3:1:1. In conclusion, these findings can be used to improve the rearing of An. funestus under laboratory conditions, improving evaluations for SIT. Feeding defibrinated bovine blood through an artificial system will reduce the dependency on live animals for blood-feeding. Optimised larval feeding and rearing density will reduce developmental time and ensure maximal pupal production. An irradiation dose of 100 Gy can be used to induce sterility of An. funestus without significantly affecting mating competitiveness.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Anopheles funestus; Laboratory-rearing; Sterile insect technique; Optimisation; Irradiation; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education